Uncommon abdominal “egg-shelled” lesions mimic hepatic echinococcosis: Two cases report - Liao, Yubo; Zhou, Guo; Yang, Chong; Zhang, Yu (Frontiers in Surgery, 2022)
Background: Primary abdominal “egg-shelled” lesions with positive anti-echinococcus IgG antibody were misdiagnosed as echinococcosis. Case presentation: Herein we report two cases with primary abdominal “egg-shelled” lesions were misdiagnosed as echinococcosis. Case 1: A 44-year-old woman presented to our department with a history of slight abdominal pain for 4 months. After admission, the laboratory tests indicated a positive anti-echinococcus IgG antibody status. The contrast-enhanced CT scan showed a 12×12 cm“egg-shelled”mass located in the hepatorenal area. The patient had the entire mass and the right adrenal gland resected. This patient recovered smoothly and was discharged uneventfully 20 days after the operation. The pathologic diagnoses was adrenal lymphangioma. Case 2: A 55-year-old woman was admitted with a history of an abdominal mass for over 10 years. After admission, her anti-echinococcus IgG antibody was positive. The contrast-enhanced CT scan revealed a heterogeneous, solid mass measuring 10×9×8cm in the right hepatic lobe. A laparoscopic exploration was performed, and the surgery revealed that the mass arose from the retroperitoneal tissue rather than the liver. Finally, the pathologic diagnoses were paraganglioma with necrosis and cystic changes. Conclusion: Enhanced CT scan and contrast-enhanced ultrasound scans are important for distinguishing echinococcosis disease from the other “egg-shelled” lesions. Surgical resection is the main treatment method for this disease. Minimally invasive surgery is recommended but should be performed by experienced surgical teams. Immunohistochemical examination is important for the pathologic diagnosis.